A new technique for filter packing water wells: research and development - Gorla, Maurizio (Acque Sotterranee - Italian Journal of Groundwater, 2014)
The selection of poor quality natural sand and gravel filter pack media for water supply wells leads to insufficient hydraulics, increased well clogging, higher electrical energy demand, reduced life-cycle and increased Operations & Maintenance (O & M) activities and costs.